Effects of corudum in the development of structural mechanical and tribological propietes of raw materials for the manufacture of structural products (2018)
Improving the technological properties of a ceramic product without affecting its aesthetic quality is a daily challenge of the regional ceramic companies. To achieve this objective, analyzes were performed on an illitic-kaolinitic clay by adding corundum as an additive. The corundum content varied from 5% to 20% by weight with a particle size of less than 75 μm, being able to obtain products with low porosities and high mechanical resistance. This research is part of a series of studies carried out on an argillaceous raw material from the region of Norte de Santander (Colombia). The influence of the corundum content on the technological properties was evaluated. The results showed that corundum, when mixed with traditional raw materials, offers the conditions to be used as an additive in the production of ceramic products with increases of up to 67% in mechanical strength and a reduction of porosity of 46%, which can contribute to the development of value-added ceramic products for use in other technological applications.